Memperkuat UMKM di Pasar Kuliner: Identitas Merek dan Inovasi Pemasaran Digital Untuk Haochi Bites - Aerish Theodora Budi Sentoso; Aerith Theodora Budi Sentoso; Cynthia Kamal; Febby Yen Gunawan; Nathania Gracia Christabella; Valentino Valentino; Wina Hudoyo; Santi Rimadias (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2024)
Micro, Small, and Medium Enterprises (MSMEs) show greater flexibility in adapting to market changes compared to large companies. They have the resilience to survive in challenging economic conditions, such as the global economic crisis or pandemic. One of the MSMEs in Indonesia, Dimsum Haochi Bites, shows strong potential in the local culinary market due to its distinctive taste and high-quality raw materials. However, its growth has been hampered by a lack of developed brand identity and limited digital marketing efforts. This community service activity aims to overcome these challenges by assisting Haochi Bites in creating a strong brand identity and expanding its digital marketing presence. The program begins with a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to identify internal and external factors that affect business performance. Furthermore, customized business support is provided, which results in the development of a new business logo and an improved digital marketing strategy through social media. In addition, the team facilitated product innovation by introducing new topping and sauce variants. The results of this community service activity increase the competitiveness of Haochi Bites and increase its market potential in the culinary sector in Tangerang.